Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper estimates potential output and the output gap in Russia. Estimating potential output in Russia is difficult because its economy is large and complex, in transition, and dependent on oil. First, Russia presents large territorial and sectoral heterogeneity. Second, structural issues are difficult to estimate in transition economies. Third, the energy sector dominates exports and GDP, making Russia vulnerable to large terms of trade shocks. This paper estimates potential output taking into account these challenges and using a variety of methodologies. The results obtained show that the output gap in Russia exhibits high uncertainty.